Effects of leadership and reward systems on employees' motivation and job satisfaction: an application to the Portuguese textile industry - Leitão, Mariana (2022)
Purpose – This study explores the perception of employees in textile industry firms in Northern Portugal regarding the influence of leadership and reward systems (RS) on their motivation (intrinsic and extrinsic) and job satisfaction (JS). Design/methodology/approach – A questionnaire was addressed to the employees of 12 firms, obtaining a sample of 256 valid responses, for which a structural equation model was estimated. Findings – The results showed that leadership and RS influence JS only through the mediating effects of intrinsic and extrinsic motivation. Originality/value – This study makes empirical and theoretical contributions, testing the relationship between leadership and employees’ JS and how this relationship can be mediated by RS, and motivation – both intrinsic and extrinsic. Moreover, this study was conducted in Portugal, country where these issues have not been researched jointly before.